2021
DOI: 10.1111/jocd.14496
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of tranexamic acid mesotherapy versus oral tranexamic acid in patients with melasma undergoing Q‐switched fractional 1064‐nm Nd:YAG laser: A blinded RCT and follow‐up

Abstract: Background: Melasma is a common hyperpigmentation disorder. This study aimed to compare the efficacy of Nd-Yag fractional 1064 plus microinjection of tranexamic acid versus Nd-Yag fractional 1064 plus oral tranexamic acid in patients with melasma. Materials and methods:This is a prospective, randomized study with a sample size of 40 patients, 20 in each treatment arm, which was done six times with 2-week intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In this study, patients with melasma were studied by two methods, Nd‐Yag Fraction 1064 + microinjection of TA and Nd‐Yag Fraction 1064+ oral TA. The result of this study showed that there is no significant relationship between micro injection and oral methods but the oral use of TA is much more tolerable for patients 31 …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, patients with melasma were studied by two methods, Nd‐Yag Fraction 1064 + microinjection of TA and Nd‐Yag Fraction 1064+ oral TA. The result of this study showed that there is no significant relationship between micro injection and oral methods but the oral use of TA is much more tolerable for patients 31 …”
Section: Discussionmentioning
confidence: 77%
“…The result of this study showed that there is no significant relationship between micro injection and oral methods but the oral use of TA is much more tolerable for patients. 31 As mentioned, TA can affect vascular component of skin and its effects on skin manifestations of rosacea was shown in a study conducted in 2019. It was found that application of TA can have significant effects on the erythema of rosacea and the severity score of rosacea significantly improved.…”
Section: Discussionmentioning
confidence: 92%
“…Then, by screening the titles and abstracts, we further eliminated 793 studies. Ultimately, 39 randomized clinical trials 12,18–55 were included in the network meta‐analysis. The flowchart of screening and selection is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pigment particles quickly expand and burst after absorbing enormous laser energy in an instant, and the cellular framework can be thoroughly preserved and repaired 26 . After being broken, pigment particles are gradually swallowed up by phagocytes and discharged from the body, resulting in the decrease of local pigment in lesions 27,28 . At the same time, the thermal energy generated by the interaction between laser and human tissue is effectively limited in the target tissue, thus avoiding the thermal damage of surrounding tissues 29 .…”
Section: Discussionmentioning
confidence: 99%